2006
DOI: 10.1037/0012-1649.42.6.1116
|View full text |Cite
|
Sign up to set email alerts
|

Popularity, social acceptance, and aggression in adolescent peer groups: Links with academic performance and school attendance.

Abstract: This article reports a short-term longitudinal study focusing on popularity and social acceptance as predictors of academic engagement for a sample of 342 adolescents (approximate average age of 14). These youths were followed for 4 consecutive semesters. Popularity, social acceptance, and aggression were assessed with a peer nomination inventory, and data on academic engagement were obtained from school records. For adolescents who were highly aggressive, increases in popularity were associated with increases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
162
4
17

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(189 citation statements)
references
References 81 publications
(99 reference statements)
6
162
4
17
Order By: Relevance
“…Such studies of relationship processes are important to pursue to understand the connection between popularity and aggression more completely. Schwartz, Gorman, Nakamoto, and McKay ( 2006 ), for example, found that, across grades 9 and 10 in a sample of lower -class youth, as perceived popularity increased, so did inattentiveness to school, but only among youth who are high in aggression. Rose, Swenson, and Waller ( 2004 ) reported that the association between relational aggression and poor friendship quality was Investigators have attended to characteristics beyond aggression as correlates of popularity, finding that sociometric popularity is generally associated with positive adjustment and prosocial behavior, whereas correlates of perceived popularity are not as clear (Becker & Luthar, 2007 ;Cillessen & Rose, 2005 ).…”
Section: Correlates Of Popularitymentioning
confidence: 99%
“…Such studies of relationship processes are important to pursue to understand the connection between popularity and aggression more completely. Schwartz, Gorman, Nakamoto, and McKay ( 2006 ), for example, found that, across grades 9 and 10 in a sample of lower -class youth, as perceived popularity increased, so did inattentiveness to school, but only among youth who are high in aggression. Rose, Swenson, and Waller ( 2004 ) reported that the association between relational aggression and poor friendship quality was Investigators have attended to characteristics beyond aggression as correlates of popularity, finding that sociometric popularity is generally associated with positive adjustment and prosocial behavior, whereas correlates of perceived popularity are not as clear (Becker & Luthar, 2007 ;Cillessen & Rose, 2005 ).…”
Section: Correlates Of Popularitymentioning
confidence: 99%
“…Possibly these measurement problems of popularity may depend on the specific school environments. It is well-established that the attributes which constitute popularity in a school environment can vary greatly (Schwartz, Gorman, Nakamoto, & McKay, 2006). Thus, in future research special care should be given to the development of a more reliable measurement of popularity and consideration of the potential differences in school contexts.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, popular youth who engage in aggressive-disruptive behavior possess popularity while exhibiting such behavior. They may, therefore, view delinquent acts as elemental to their identity and popular status and engage in early alcohol use to demonstrate their rebelliousness in order to maintain popularity, similar to processes hypothesized regarding school disengagement (Schwartz et al, 2006).…”
Section: Popularity As a Moderatormentioning
confidence: 99%